Design, manufacturing and characterization of biodegradable bone screw from PLA Prepared by fused deposition modelling (FDM) 3D printing technique - Ismail, Rifky; Fitriyana, Deni Fajar; Bayuseno, Athanasius Priharyoto; Munanda, Rafi; Nugraha, Fariz Wisda; Rusiyanto, R.; Setiyawan, Andri; Bahatmaka, Aldias; Firmansyah, Hendrix Noviyanto; Anis, Samsudin; Irawan, Agustinus Purna; Siregar, Januar Parlaungan; et al. (Semarak Ilmu Publishing, 2023)
Biopolymers are utilized extensively in the medical field. The production of biodegradable bone screws for bone implants utilizing biopolymer materials is one of the advances developments. Polylactic acid (PLA) is a biopolymer frequently employed in medicinal applications. Using 3D printing, this research was done to create a biodegradable bone screw derived from PLA. The 3D printing process was chosen to reduce the cost and duration of bone repair. A nozzle temperature of 210oC and a bed temperature of 60oC are utilized in the production of biodegradable PLA screws. The torque test, fracture analysis, density test, and biodegradation test were utilized to characterize biodegradable bone screws. The results of this study will be compared with commercial biodegradable bone screws (BIOSURE HA). The findings of torsion tests indicate that commercially biodegradable bone screws have superior clamping quality than PLA-based biodegradable bone screws. The degradation rate of commercial biodegradable bone screws is greater than that of PLA-based biodegradable bone screws. In addition, commercial bone screws are denser than PLA-based biodegradable bone screws